Evaluating sleep's role in type 2 diabetes mellitus: Evidence from NHANES - Jijun Zhang; Chuanli Yang; Jie An; Yunhe Fan; Xiushan Dong (Brain, Behavior, & Immunity - Health, 2025)
Background: Evidence is limited regarding the relationship between sleep factors (self-reported sleep disorder diagnosis, subjective sleep difficulties, and sleep duration), sleep patterns, and risk of type 2 diabetes mellitus (T2D). Thus, this study aims to investigate the relationship between sleep factors, sleep patterns, and the risk of T2D using data from the National Health and Nutrition Examination Survey (NHANES). Methods: A total of 14,652 individuals aged ≥18 years from the NHANES (2005–2014) were enrolled with complete data on sleep factors, T2D, and covariates. Information on self-reported sleep disorder diagnosis, subjective sleep difficulties, and sleep duration was collected during in-home visits by trained interviewers using the Computer-Assisted Personal Interviewing system. The sleep pattern was derived from scoring three mentioned factors: no self-reported sleep disorder diagnosis, no subjective sleep difficulties, and sleep duration of 7–9 h were classified as low-risk (score 0), while the presence of self-reported sleep disorder diagnosis, subjective sleep difficulties, or sleep duration <7 or >9 h were classified as high-risk (score 1). Cumulative scores range from 0 to 3, with 0 indicating a healthy sleep pattern, 1 an intermediate sleep pattern, and 2–3 a poor sleep pattern, respectively. Weighted logistic regression was conducted to assess the association of sleep factors and sleep patterns with the risk of T2D. Results: Self-reported sleep disorder diagnosis (odds ratio (OR) = 1.32, P = 0.01), subjective sleep difficulties (OR = 1.29, P = 0.001), and sleep deprivation (<7 h; OR = 1.20, P = 0.01) were significantly positive with T2D. Poor sleep pattern also significantly increased T2D risk (OR = 1.52, P < 0.0001). Moreover, subgroup analyses stratified by age and BMI (body mass index) further confirmed that the positive association between sleep patterns and T2D was consistent and robust across groups. Conclusion: Our findings indicate that poorer sleep patterns are associated with an increased risk of T2D. These results emphasize the importance of sleep management in T2D prevention. Further prospective studies are needed to investigate the causal or bidirectional relationship between sleep and T2D risk, as well as the underlying molecular mechanisms.